A Descriptive Study of the Relationship between Moral Values and Social Acts on a Sample of Students from the University of King Abdulaziz - Seham Ahmed Alazab (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
The present study aims at identifying the relationship between moral values and social acts in the light of Max Weber’s theory of action in terms of some demographic variables (i.e., gender, place of residence, academic level, and academic specialization) of some college students. It is applied to sample consisting of 360 students at King Abdul Aziz University in Jeddah. The study tools included demographic data form and two criteria of measurements: moral values and social act. The statistical calculations are performed by the Arithmetic Mean, Standard Deviation, T-test and Pearson correlation. The results revealed that the correlation and congruence between moral values and social acts are much clearer in female sample than the male sample, and in the village residents than the civilian ones, and in the students of the college level (1-4) than the college level (5-8).